Prosedur Pemeriksaan MRI Cervical Dengan Diagnosa Cervical Root Syndrome (CRS) di Instalasi Radiologi RSUD DR. Moewardi - Denita Puspita Sari; Ni Putu Rita Jeniyanthi; Ni Luh Putu Sari Widari (Jurnal Ilmu Kesehatan dan Gizi, 2024)
CRS occurs when there is irritation to the cervical nerve roots due to the vertebral disc bulging out. In diagnosing CRS, supporting tools such as MRI are needed. The purpose of this study was to determine how the cervical MRI examination procedure with a diagnosis of CRS at the Radiology Installation of Dr. Moewardi Hospital and why the cervical MRI examination with a diagnosis did not use the T2*GRE and Proton Density sequences. This study used a qualitative method with a case study approach conducted from June-July 2023 with the object of research as many as five patients diagnosed with CRS. The respondents consisted of three radiographers, three radiology specialists, and one sending doctor. The cervical MRI examination procedure with a diagnosis of CRS at the Radiology Installation of Dr. Moewardi Hospital has no special preparation, the patient only releases metal objects in the patient's body before entering the examination room. The sequences used are Coronal T1 FSE, Coronal STIR, Sagittal T2 FRFSE, Sagittal T1 FSE, Sagittal STIR, Axial T2 FRFSE, Axial T1 FSE, and Myelography. Based on the results of the study, using T2*GRE in CRS diagnosis will produce a poor picture. While Proton Density is good for bone but because of the use of a long time and CRS diagnosis is more focused on nerve fibers and soft tissue, it does not need to be used.